Multicast routing for mesh-based using DSR in wireless sensor network - C.R, Manjunath; S. Nagaraja, G (International Journal of Engineering and Technology, 2018)
Multicast routing is helpful to establish group communication for sharing, transmitting the data or message from one stream to another stream within a network. The Multicasting Routing protocol is a vast challenging research area. Different routing algorithms erect based upon various domain or various applications. Some common on-demand multicasting routing algorithms are DSR, DSDV and Wireless Routing Protocol (WRP). The usage of multicasting in DSR has many advantages. It can reduce the cost of transmission and improves efficiency when transmitting information between wireless networks. The major complexity for designing a routing protocol in network is the dynamic change in the topology, due to random movement of nodes. When large number of nodes is deployed over a network, we use multicast approach to find the optimal path to the multiple destinations. In this paper, using MATLAB tool, find the parameters like time and energy consumed for mesh network using DSR mesh-based routing protocol and find optimal path using energy efficient multicast approach.